Dios Nos Hizo Diferentes: Children's Spiritual Activism in an EFL Classroom - Angie Marroquin; Anna Carolina Peñaloza (Asociación Colombiana de Profesores de Ingles, 2024)
Though language education and research have pushed back against traditional, hegemonic ways of teaching, they continue to exclude conversations on spirituality. Moreover, a deficit lens in language education perpetuates a focus on what needs to be improved rather than on our students' assets. In this pedagogical intervention, we begin by weaving the work of feminists of color to discuss what asset-based, desired-based research and feminist pedagogy can contribute to understanding children's spiritual activism. We worked with 31 fourth graders in a private school in Duitama, Colombia. As the study took place during the pandemic and mass mobilizations, the children shared their spirituality to cope with reality. Furthermore, the children's spirituality demonstrated their belief in a higher power, positive emotions to comfort others, hope for a better future, and an understanding of equity based on race and gender. We invite language educators and researchers to create spaces for children to share their spiritual activism through the integration of feminist pedagogy focused on asset and desire-based approaches.